Medullary carcinoma of the thyroid metastatic to the breast: a case report and literature review - Martins, Sebastião Nunes (Autops Case Rep, 2014)
Breast malignancies, apart from skin cancer, are the leading cause of cancer from cancer among the female population. Unlike the high prevalence of primary mammary malignancies, metastases to the breast are uncommon, and account for only 0.2-2.7% of all malignancies affecting this organ. We report the case of a 35-year-old woman who sought medical care because of a breast lump. A mammogram suggested a breast tumor, which was biopsied. The histopathological workup resulted in the diagnosis of a metastasis from a medullary thyroid cancer. The authors review the most useful clinical, radiological, histological, and immunohistochemical features concerning extramammary malignancy to the breast.